ANALISIS PENGENDALIAN KUALITAS PRODUK MENGGUNAKAN METODE SIX SIGMA DAN FMEA PADA PERUSAHAAN MANUFAKTUR LOGAM - Fatoni, Febriyanto Arifiyan; Ferida Yuamita (JURNAL ILMIAH RESEARCH STUDENT, 2026)
competitiveness of manufacturing companies. PT. XYZ, as a manufacturer of aluminum alloy components, still faces quality issues in the die casting process. Based on production data of Intake K59 in August 2025, the defect rate reached 3.42%, or 68 units out of a total of 1,986 units produced. The dominant types of defects include porosity at 62%, incompleteness at 16%, and warping at 15%. This high defect rate impacts productivity decline, increased production costs, and reduced process efficiency. This study aims to identify the main causes of defects and determine the appropriate improvement priorities. The methods used are Six Sigma with the DMAIC approach and Failure Mode and Effect Analysis (FMEA). Six Sigma is used to evaluate process quality performance, while FMEA serves to determine improvement priorities based on the Risk Priority Number. The research results show that material factors have the highest RPN values 480, making them the main focus for improvement.